2003
DOI: 10.1080/0265203021000055405
|View full text |Cite
|
Sign up to set email alerts
|

2001 survey of organochlorine pesticides in retail milk from Beijing, P. R. China

Abstract: A monitoring study was conducted in 2001 to determine the organochlorine pesticides and their metabolite residues in milk taken from supermarkets in Beijing, P. R. China. The average concentrations of total HCH and DDT were 0.038 and 0.046 mg x kg(-1), respectively, expressed on a fat basis. The aldrin residue was detected in nine milk samples, with a mean concentration of 0.035 mg x kg(-1). Heptachlor and its epoxides were not found in any milk samples. Of 72 milk samples analysed, three from South China cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
0
14
2
Order By: Relevance
“…The mean level of a-HCH (0.0188 mg/kg) in the milk samples of present study was similar or less than those reported in few other studies conducted in India (Mukherjee and Gopal 1993), Spain (Riva and Anadon 1991), Mexico (Waliszewski et al 1996) and China (Zhong et al 2003) but still higher than those detected in France (Venant et al 1991) and Slovakia (Prachar et al 1995). In case of b-HCH, however, the mean concentration obtained in the present study (0.0985 mg/kg) was comparable only with that of Mexico (Waliszewski et al 1996) and on the higher side compared to all other reports as mentioned in Table 2.…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…The mean level of a-HCH (0.0188 mg/kg) in the milk samples of present study was similar or less than those reported in few other studies conducted in India (Mukherjee and Gopal 1993), Spain (Riva and Anadon 1991), Mexico (Waliszewski et al 1996) and China (Zhong et al 2003) but still higher than those detected in France (Venant et al 1991) and Slovakia (Prachar et al 1995). In case of b-HCH, however, the mean concentration obtained in the present study (0.0985 mg/kg) was comparable only with that of Mexico (Waliszewski et al 1996) and on the higher side compared to all other reports as mentioned in Table 2.…”
Section: Resultscontrasting
confidence: 49%
“…Being a fat rich food it is an important source of OCP accumulation and hence one of the convenient food stuff for measuring the persistent OCPs. It is recommended by the United Nations Environment Programme (UNEP) as an indicator of POPs (UNEP 2001) and has been studied in various surveys (ICMR 1993;Mukherjee and Gopal 1993;Kumar and Nath 1996;Waliszewski et al 1996;Wong and Lee 1997;Kalra et al 1999;John et al 2001;Nigam and Siddiqui 2001;Pandit et al 2002;Vasanthi et al 2003;Zhong et al 2003;Pardio et al 2003;Waliszewski et al 2003;Battu et al 2004;Surendranath et al 2005). The present paper reports here the status of the organochlorine residues in milk intended for human consumption, collected from different places of Bundelkhand region of India like Jhansi, Lalitpur, Banda, Gwalior, Jalaun, Rath, Tikamgarh, Chhatarpur, Sagar, Panna and Bhind.…”
mentioning
confidence: 99%
“…The residue of HCH and DDT-R detected in the milk samples were well below MRL values. Zhong et al (2003) reported organochlorine pesticides and their metabolite residues in milk taken from super markets in Beijing, China. The average concentrations of total HCHand DDT were0.038 and 0.046 mg kg -1 on a fat body respectivety.…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of pesticides in China: more in the breach than the observance? Although many pesticides have been regulated in the PRC since the 1950s, illicit manufacturers in China continue to produce not only domestically banned organochlorine compounds such as DDT, but also a number of highly toxic rodenticides (Zhong et al 2003). Sales of these compounds are often conducted in large open markets with informal marketing and retail distribution networks.…”
Section: The Legal and Illicit Market For Rodenticides In Chinamentioning
confidence: 99%